Disclosure of Financial Reporting of Islamic Financial Institutes of Bangladesh: A Concept of Relevant Reviews - Mohammad Shamsus Sadekin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Islamic banking is a system of banking that avoids receipt and payment of interest in its transactions and conducts its operations in accordance with Shariah principles to achieve the objectives of Islamic economy. The main objective of this review paper is to compare the level of disclosure of information by the Islamic Banking sector in Bangladesh. Multiple linear regression techniques will be used to test the hypotheses under study. The findings of this review paper is the supervisory authorities should recognize the need to set up a regulatory framework that, while consistent with Islamic precepts, would be pragmatic and flexible enough to meet internationally-accepted prudential and supervisory requirements. Effective prudential supervision of Islamic Banks in their home countries is important to foster integration between Islamic and conventional banking systems.